2003
DOI: 10.1590/s0004-282x2003000400027
|View full text |Cite
|
Sign up to set email alerts
|

Isolated oculomotor nerve palsy inspontaneous internal carotid artery dissection: case report

Abstract: -Partial oculosympathetic palsy followed by ischemic manifestations in brain or retina are the main symptoms of extracranial internal carotid artery (ICA) dissection. Unusually, cranial nerves may be affected. Isolated oculomotor nerve palsy is found only rarely. Case: We present a 50-year-old nondiabetic man who experienced acute onset of right occipital headache which spread to the right retro-orbital region. Five days later he noticed diplopia and right blurred vision sensation. Neurologic examination discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…According to previous descriptions (CAMPOS, MASSARO and SCAFF, 2003), pupillary involvement is not a rule, but in some cases mydriasis may be the only manifestation for the few days preceding the complete oculomotor nerve palsy. In other patients the pupil tends to be miotic, presumably because of the concurrent oculosympathetic palsy due to the pericarotid sympathetic plexus involvement.…”
Section: Discussionmentioning
confidence: 94%
“…According to previous descriptions (CAMPOS, MASSARO and SCAFF, 2003), pupillary involvement is not a rule, but in some cases mydriasis may be the only manifestation for the few days preceding the complete oculomotor nerve palsy. In other patients the pupil tends to be miotic, presumably because of the concurrent oculosympathetic palsy due to the pericarotid sympathetic plexus involvement.…”
Section: Discussionmentioning
confidence: 94%
“…Campos, C.R., et al, reported a 50-year-old non-diabetic man who experienced acute onset right sided headache, impaired adduction and upward gaze of right eye and slight ipsilateral pupillary dilatation without ptosis. His angiography showed right ICA dissection with forward occlusion to the base of the skull [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Posteriorly, posterior cerebral and cavernous portion of internal carotid branches, give rise other vessels for the network [2]. This pattern of blood supply, coming from different arterial territories, could explain why oculomotor palsy is very uncommon, even transiently, after carotid occlussions or carotid ligation during treatment of aneruysms [4] since occlusion of several components of the nerves nutrient supply is probably required to produce significant ischemia [68]. …”
Section: Discussionmentioning
confidence: 99%
“…But, in the past few years, several clinical cases of binocular diplopia caused by oculomotor nerve palsies have been described associated with stenosis or occlusion of the ICA [2, 3]. The majority of these cases have been reported on young patients with arterial dissection and few cases in patients after radiation induced atherosclerosis [4, 5]. …”
Section: Introductionmentioning
confidence: 99%